PRONOMINA BAHASA JAWA TENGAH DIALEK SOLO - Suharti, Sri; Charlina, Charlina; Sinaga, Mangatur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The aim of this research is to describe the types of Central Java Solo dialect pronomina. The data is formed the informant’s pronouncement as personal prononima, direction pronomina and introgative pronomina on Central Java Solo dialect. This reseach is qualitative reseach using descriptive method. Thetecnique are interviewing, taking notes, and recording. The data were analyzed by using pronomina data which is already gathered, observed the data, clasified the types of pronomina, selected and grouped the data, analyzed and summarized the data. The result shows that the pronomina of Central Java are persona pronomina, direction pronomina and introgative pronomina. Persona pronomina are first pronomina, second pronomina and third pronomina which is devided by singular and plural types. The examples of persona pronomina Central Java Solo dialect are aku, kulo, dhewe’e, kowe, sampeyan, panjenengan, kowe kabeh, panjenengan sedoyo, dhe’e, wong iku dan tiang niku.While the direction pronomina are devided as a public direction pronomina, place direction pronomina, and things direction pronomina. The examples of direction pronomina Central Java Solo dialect are iki, iku, niki, niku, kene, kono, ngene, ngono, ngeten, and ngono. The examples of introgative pronomina Central Java Solo dialect are iki, iku, niki, niku, kene, kono, ngene, ngono, ngeten, dan ngoten. Meanwhile, the intogative pronomina are opo, nopo, sopo, sinten, ngopo, kenging nopo, piro, pinten, kepiye, pripun, endi, pundi, and kapan.Key words: pronomina, persona pronomina, direction pronomina, introgative pronomina.